PERANCANGAN PROTOTYPE APLIKASI MOBILE LITERASI DAN MANAJEMEN KEUANGAN UNTUK GENERASI PRODUKTIF MENGGUNAKAN METODE DESIGN THINKING - Ferdyansyah, Syahrul; Susanti, Aisah Rini; Gunadi, Gugun (Jurnal Algoritma, Logika dan Komputasi, 2026)
adults aged 18–25. However, high usage of financial applications is not always supported by sufficient financial literacy, resulting in a gap between the ability to use digital tools and to manage personal finances effectively. This study aims to design a mobile prototype called “KELOLA” to support financial literacy and personal financial management for young users. The research applies the Design Thinking approach, including Empathize, Define, Ideate, Prototype, and Test stages. The interface was created in Figma to produce an interactive high-fidelity prototype. Usability testing was conducted using Heuristic Evaluation with four evaluators experienced in UI/UX. The assessment focused on six heuristic principles, including system visibility, real-world match, user control, minimalist design, flexibility, and error handling. The results show that most indicators received low severity scores (0–1), indicating only minor usability issues that did not disrupt user flow. Overall, the KELOLA prototype demonstrates good usability and has strong potential for further development.